"Zipper‐like" periodic magnetosonic waves: Van Allen Probes, THEMIS, and magnetospheric multiscale observations. Issue 2 (8th February 2017) - Li, J.; Bortnik, J.; Li, W.; Ma, Q.; Thorne, R. M.; Kletzing, C. A.; Kurth, W. S.; Hospodarsky, G. B.; Wygant, J.; Breneman, A.; Thaller, S.; Funsten, H. O.; et al.
Abstract: An interesting form of "zipper‐like" magnetosonic waves consisting of two bands of interleaved periodic rising‐tone spectra was newly observed by the Van Allen Probes, the Time History of Events and Macroscale Interactions during Substorms (THEMIS), and the Magnetospheric Multiscale (MMS) missions. The two discrete bands are distinct in frequency and intensity; however, they maintain the same periodicity which varies in space and time, suggesting that they possibly originate from one single source intrinsically. In one event, the zipper‐like magnetosonic waves exhibit the same periodicity as a constant‐frequency magnetosonic wave and an electrostatic emission, but the modulation comes from neither density fluctuations nor ULF waves. A statistical survey based on 3.5 years of multisatellite observations shows that zipper‐like magnetosonic waves mainly occur on the dawnside to noonside, in a frequency range between 10 f cp and f LHR . The zipper‐like magnetosonic waves may provide a new clue to nonlinear excitation or modulation process, while its cause still remains to be fully understood. Key Points: "Zipper‐like" magnetosonic waves consist of two‐frequency bands with interleaved periodic emissions The two bands differ in frequency and intensity but probably originate from one single source Zipper‐like magnetosonic waves were mainly observed on dawnside to noonside in frequencies between 10 f cp and f LHR .